A new use of frame-of-reference training: improving reviewers’ inferences from biodata information - Lundstrom, Joel Thomas (Kansas State University, 2007)
A commonly accepted practice in employment selection is to collect biographical information in the form of resumes. Surprisingly, little research is conducted in this area to learn how reviewers evaluate relevant biographical information and considerable less research is devoted to exploring possible methods on how to improve this evaluation process. Current research explored one possible training method that may later show great utility in improving accuracy and consistency in ratings for a number of work-related constructs. Frame-of-reference training, which is primarily utilized in the field of performance appraisal, was hypothesized to be a beneficial training technique in an effort to improve accuracy. Frame-of-reference (FOR) training attempts to create a common frame of reference among raters when assessing rates' behaviors. Through a process of practice and feedback, FOR training tunes raters to common notions of what good or poor would be on a particular dimension. The result is often more accurate ratings with less variation between raters. Personality (conscientiousness, extraversion, and agreeableness only), general cognitive ability, and organizational citizenship behaviors were the constructs of interest. The analysis provided initial support for most of the hypotheses which suggested that frame-of-reference training would create more accurate and reliable estimates of applicant's personality, cognitive ability, and even organizational citizenship behaviors. In addition to influencing participants' estimates of applicant's scores on a number of workplace constructs, it was also found that participants were influenced as a function of type of training on their willingness to interview and overall impressions of the applicants. Limitations and suggestions for future research are also discussed.
Keywords: Frame-of-reference training; Biodata; Biographical information blanks; Resumes; Personality; Selection; Business Administration, Management (0454); Psychology, General (0621); Psychology, Industrial (0624)